2019
DOI: 10.1097/shk.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA, H19 Mediates the Protective Effect of Hypoxia Postconditioning Against Hypoxia-Reoxygenation Injury to Senescent Cardiomyocytes by Targeting microRNA-29b-3p

Abstract: These findings suggest that H19 mediated the antiapoptotic effect of H/Post against H/R-induced injury to aged cardiomyocytes by inhibiting miR-29b-3p expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…1,5,19 Interestingly, investigators have verified that H19 is a key mediator involved in myocardial inflammatory reactions and apoptosis. 12,30,31 Consistent with these previous studies, the data from our study clearly illustrated that H19 up-regulation not only significantly If we are only at the beginning of understanding the role of H19 in AMI, we are even further away from comprehending the underlying mechanism. The competing endogenous RNA (ceRNA) theory has shed new light on how H19 participates in the pathological process of AMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1,5,19 Interestingly, investigators have verified that H19 is a key mediator involved in myocardial inflammatory reactions and apoptosis. 12,30,31 Consistent with these previous studies, the data from our study clearly illustrated that H19 up-regulation not only significantly If we are only at the beginning of understanding the role of H19 in AMI, we are even further away from comprehending the underlying mechanism. The competing endogenous RNA (ceRNA) theory has shed new light on how H19 participates in the pathological process of AMI.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation and apoptosis are two crucial factors that contribute to AMI and the subsequent cardiac remoulding . Interestingly, investigators have verified that H19 is a key mediator involved in myocardial inflammatory reactions and apoptosis . Consistent with these previous studies, the data from our study clearly illustrated that H19 up‐regulation not only significantly reduced the expression of the pro‐inflammatory factors IL‐6 and TNF‐α but also decreased the number of TUNEL‐positive cells and the ratio of Bax/Bcl‐2 in the context of AMI.…”
Section: Discussionsupporting
confidence: 91%
“…it was found that H19 overexpression alleviated hypoxia-induced injury mediated apoptosis, cell cycle arrest and mitochondrial membrane potential depolarization; however, these processes were aggravated by H19 knockdown. These results suggested that H19 attenuated hypoxia-induced myocardial cell injury, which is consistent with previous studies (15,16). The findings of this previous report (16) and the present study are consistent with each other in regard to the molecular mechanism of H19 in protecting against myocardial i/r injury.…”
Section: Discussionsupporting
confidence: 93%
“…increased expression of H19 was detected in rats following surgically induced myocardial i/r, suggesting that H19 may have a role in the protective mechanisms against i/r injury (14). Previous studies have also indicated that H19 exerts protective effects against hypoxia-induced injury in cardiomyocytes (15,16). nevertheless, to date, the functional role of H19 in myocardial hypoxic injury has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 93%
“…The binding sites were verified by luciferase reporter gene assays. Indeed, the H19/miR-29b-3p/cIAP1 axis was revealed to play an important role in aged cardiomyocyte apoptosis [17]. However, whether Dex postconditioning can attenuate I/R injury by regulating H19 remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%